2013
DOI: 10.3402/fnr.v57i0.19621
|View full text |Cite
|
Sign up to set email alerts
|

Reporting accuracy of packed lunch consumption among Danish 11-year-olds differ by gender

Abstract: BackgroundPacked lunch is the dominant lunch format in many countries including Denmark. School lunch is consumed unsupervised, and self-reported recalls are appropriate in the school setting. However, little is known about the accuracy of recalls in relation to packed lunch.ObjectiveTo assess the qualitative recall accuracy of self-reported consumption of packed lunch among Danish 11-year-old children in relation to gender and dietary assessment method.DesignA cross-sectional dietary recall study of packed lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
8
1
2
Order By: Relevance
“…There were improved (but still not acceptable) accuracy measures in the 2 other studies when shorter retention periods were used. Five (31,34,44,45,47) of the 8 studies (31,37,40,44,(44)(45)(46)(47), which conducted school meal recall the same day as when consumption took place, still reported poor accuracy for reported food items. One study reported significant increases in match rates with any prompting (47) whereas another reported no changes in accuracy measures when prompting was used (33).…”
Section: Methodological Evidence On the Relative Accuracy And Reliability Of Dietary Assessment Toolsmentioning
confidence: 99%
“…There were improved (but still not acceptable) accuracy measures in the 2 other studies when shorter retention periods were used. Five (31,34,44,45,47) of the 8 studies (31,37,40,44,(44)(45)(46)(47), which conducted school meal recall the same day as when consumption took place, still reported poor accuracy for reported food items. One study reported significant increases in match rates with any prompting (47) whereas another reported no changes in accuracy measures when prompting was used (33).…”
Section: Methodological Evidence On the Relative Accuracy And Reliability Of Dietary Assessment Toolsmentioning
confidence: 99%
“…In Denmark, provision of school cafeterias is not considered the norm, necessitating that most children attending school bring lunch from home (53,54) . Of late, there has been interest in ensuring the nutritional quality of packed school lunch, due to the introduction of school health initiatives and food policies (55) .…”
Section: Covariatesmentioning
confidence: 99%
“…We also considered behavioural correlates reflecting the school lunch context, such as the presence of a school canteen (48)(49)(50) , which may be associated with healthy eating (51,52) and minimize the likelihood of consuming lunch elsewhere. In Denmark, provision of school cafeterias is not considered the norm, necessitating that most children attending school bring lunch from home (53,54) . Of late, there has been interest in ensuring the nutritional quality of packed school lunch, due to the introduction of school health initiatives and food policies (55) .…”
Section: Covariatesmentioning
confidence: 99%
“…In children, it is generally assumed that from the age of around 10 years they can recognise and describe quantities necessary for filling out an FFQ ( 13 ) . However, adolescents are more prone to omit and intrude foods when reporting their diet compared with adults ( 13 15 ) . Even though skills in estimating portion sizes increase with age, focus on body image which seems to affect the accuracy of adolescents’ self-reported dietary intake also increases with age ( 16 , 17 ) .…”
mentioning
confidence: 99%